MARGIN MARKETING Anchovy (Stolephorus commersonii) IN WARD SEI BEROMBANG DISTRICT PANAI HILIR LABUHANBATU DISTRICT NORTH SUMATRA PROVINCE - Yulinda Suaseh Nasution; Lamun Bathara; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThe research aims to know marketing outlets, the margin and the revenue obtained marketing institutions Anchovies rice. Based on the results of research, there are two kinds of marketing outlets first is from a producer to middle-men, then into a retailer Rantauprapat traders and consumers Rantauprapat, while for the second from a producer to middle-men, then into the large Tanjung Balai Asahan, then consumers Medan, Jakarta and Malaysia.Marketing costs in a month from each of the largest marketing agencies are issued by retailers 2 Rp. 84.292/kg and the smallest is the merchant Gatherer 2 Rp 43.207/kg. Net receipts within one month of each marketing agencies is the largest obtained by the merchants for the purpose of marketing Malaysia amounting to Rp. 34.413/kg and the smallest is the retailers 2 Rp 5.708/kg.The value of marketing margins on the level of middle-men namely 28,57 %, the value of marketing margins on the level of a retailer Rantauprapat traders namely 44,44 %. Meanwhile, the value of marketing margins on their destination marketing Medan namelyJOM : Vol. 26 JANUARI 201544,44 %, area destination marketing Jakarta is 50,00 % and their destination marketing Malaysia namely 54,55 %.Keyword: Marketing Channel, Marketing Margin, Anchovies rice